Antidepressant Potential of Quercetin and its Glycoside Derivatives: A Comprehensive Review and Update - Chen, Shen; Tang, Yueheng; Gao, Yang; Nie, Kexin; Wang, Hongzhan; Su, Hao; Wang, Zhi; Lu, Fuer; Huang, Wenya; Dong, Hui (Frontiers in Pharmacology, 2022)
Depression is a global health problem with growing prevalence rates and serious impacts on the daily life of patients. However, the side effects of currently used antidepressants greatly reduce the compliance of patients. Quercetin is a flavonol present in fruits, vegetables, and Traditional Chinese medicine (TCM) that has been proved to have various pharmacological effects such as anti-depressant, anti-cancer, antibacterial, antioxidant, anti-inflammatory, and neuroprotective. This review summarizes the evidence for the pharmacological application of quercetin to treat depression. We clarified the mechanisms of quercetin regulating the levels of neurotransmitters, promoting the regeneration of hippocampal neurons, improving hypothalamic-pituitary-adrenal (HPA) axis dysfunction, and reducing inflammatory states and anti-oxidative stress. We also summarized the antidepressant effects of some quercetin glycoside derivatives to provide a reference for further research and clinical application.